Razvoj vakuumske transferne tehnike za serijsko procesiranje kanalnih fotopomnoževalk - Erjavec, Bojan (Materiali in tehnologije, 2000)
In the paper, the processing of a new generation of miniature photomultipliers exhibiting high sensitivity, fast time response, extremely low background and extended dynamic range is presented. Electron multiplication is enabled by a high-gain and extremely low-background glass channel electron multiplier serving also as a main part of enclosure of the new miniature electron tube. This continuous electron multiplier is hermetically closed at its exit and input with anode and cathode subassembly, respectively. Due to small volume of the new channel photomultipliers, all important phases like tube subassemblies preparation, photocathode processing, transferring and sealing the photocathode faceplates with the tube bodies take place in ultra high vacuum (UHV) using a transfer technique, based on and developed from the vacuum transfer technique of the image intensifiers production. These new photodetectors exhibit high quantum efficiency and low thermionic emission current of processed photocathodes, low anode dark current, good single photo electron response, i.e. narrow pulse height distribution and high peak to valley ratio, and are, therefore, very useful in single photon counting applications for detection of very weak light signals.
Keywords: fotodetektorji; fotopomnoževalke; transferna tehnika